Study on current water quality status of Balok River - Nur Atiyah Izzati, W.Deraman (2016)
With two thirds of the earth's surface covered by water and the human body consisting of 75 percent of it, it is evidently clear that water is one of the prime elements responsible for life on earth. Water is an essential resource that sustains life on earth; changes in the natural quality and distribution of water have ecological impacts that can sometimes be devastating. Recently, Malaysian is facing a lot of environmental issues regarding water pollution. The aim of the study was to determine the current water quality status in the Balok River and to classify it based on Water Quality Index (DOE- WQI) and National Water Quality Index (NWQI). The sampling station were selected at three point along Balok River such as Balok River Jetty, residential area of Balok Permai and Balok Perdana which is the effluent of Gebeng industrial area and residential. The water quality parameters were measured by using standard method. The testing on parameters is divided into in-situ test and ex-situ test. Based on results it is found that Balok River was classified under class IV according to the WQI, which the river water is suitable for irrigation only. River pollution was driven by the high content of contaminants and it was reduced the oxygen content in the water. Through the testing found that there was a high concentration of BOD, COD, Ammoniacal Nitrogen and chromium and it may affect the human health and environment. Therefore, precaution to control water pollution in Balok River should be taken immediately by all parties to protect the ecosystem and environmental beauty.